Identifying optimal barriers to halt the invasion of cane toads Rhinella marina in arid Australia. Issue 1 (12th December 2012) - Tingley, Reid; Phillips, Benjamin L.; Letnic, Mike; Brown, Gregory P.; Shine, Richard; Baird, Stuart J. E.; Cadotte, Marc
Summary Spatial heterogeneity in environmental conditions may restrict the spread of invasive species to narrow corridors between extensive patches of suitable habitat; thus, we may be able to curtail invasions by identifying such corridors, and focusing control efforts in these areas. Invasive cane toads Rhinella marina have spread rapidly through northern Australia, but to invade further into Western Australia, the toads must traverse a narrow arid corridor where artificial waterbodies may serve as critical stepping stones for range expansion. We focus on the cane toads' imminent expansion into north‐western Australia and use stochastic simulation to identify areas in which removal of artificial waterbodies would be most effective at stopping their spread. Our model predicts that toads will spread from the Kimberley to the Pilbara regions of Western Australia through a narrow coastal corridor, but that they will depend upon artificial waterbodies to do so. Importantly, excluding toads from artificial waterbodies is predicted to prevent toads from colonizing c. 268 200 km2 of their potential range in Western Australia. We identified three locations where closure of a relatively small subset of artificial waterbodies is predicted to halt the spread of toads. Synthesis and applications. We present a modelling framework that can be used to focus management activities within invasion corridors. Our analyses suggest that strategic removal of potential invasion hubs along such corridors can halt the spread of an invasive species.